The in vitro effect of nanoliposomal amphotericin B against two clinically important dermatophytes. (27th June 2021) - Ahmad Nasrollahi, Saman; Fattahi, Azam; Naeimifar, Atefeh; Lotfali, Ensieh; Firooz, Alireza; Khamesipoor, Ali; Skandari, Seyed Ebrahim; Miramin Mohammadi, Akram
Abstract: Aims: The present study aimed to investigate the antifungal activity of amphotericin B‐loaded nanoliposomes against Trichophyton interdigitale and Trichophyton rubrum . Moreover, it was attempted to assess the obtained resistance in vitro . Methods: In total, 29 archived clinical strains, namely, T. interdigitale ( n = 16) and T. rubrum ( n = 13), were included in this study. These strains were determined using a previous ITS1‐ITS2 region sequence. Moreover, a liposomal formulation of amphotericin B was formulated by a thin‐film hydration method. Particle size, polydispersity index (PdI), and zeta potential (ZP) were measured by a Zetasizer. Furthermore, physicochemical properties, such as appearance, aggregation of particles, particle size, PdI, and ZP, were determined at 0‐, 1‐, and 3‐month intervals. A scanning electron microscope (SEM) was also used to examine nanoparticles structure. The minimum inhibitory concentration (MIC) of amphotericin B‐loaded nanoliposomes, itraconazole, efinaconazole, terbinafine, and ciclopirox was determined according to the protocol of the broth microdilution method of CLSI M38‐A2. The morphological changes of T. interdigitale and T . rubrum strains exposed to the amphotericin B‐loaded nanoliposomes were observed using SEM. Results: The amphotericin B‐loaded nanoliposomes displayed a lower MIC compared to those of the amphotericin B and liposomes when used separately. Based on the results, amphotericin B‐loaded nanoliposomes induced no drug resistance in any of the tested strains. Conclusion: Accordingly, amphotericin B‐loaded nanoliposomes can be a potent antifungal for the topical treatment of onychomycosis. There was no in vitro evidence regarding the resistance of the tested strains to amphotericin B‐loaded nanoliposomes. This reflects that amphotericin B‐loaded nanoliposomes have a low probability to induce drug resistance in dermatophyte species.